Some Ambiguous Features for Geologic Interpretation - H.D. Tjia (Institute for Research and Community Services (LPPM) ITB, 1969)
Abstract. Among geologic features, which do not indicate phenomena claimed by textbooks, are triangular facet developed on steeply inclined dipslopes, sensation of coarseness that does indicate the sense of fault displacement, and orientation of long pebble-axes perpendicular to transport direction, examples of these features are demonstrated.Ichtisar. Penulis telah mendjumpai beberapa gedjala geologi jang mempunjai arti berlainan dari pada jang biasa dikemukakan oleh